SONGGA WOOD (STRYCHNOS LIGUSTRINA BLUME) ASSOCIATED WITH REDUCE TUMOR NECROSIS FACTOR-ALPHA LEVELS IN ARTEMINISIN-BASED-COMBINATION THERAPY-TREATED MALARIA - Kis Djamiatun (Jurnal Kedokteran Diponegoro (Diponegoro Medical Journal), 2025)
Background: The emergence of resistance to artemisinin-based combination therapies (ACTs) complicates malaria control strategies, necessitating novel therapeutic approaches and enhanced surveillance in affected regions. Traditional herbal remedies, such as Songga wood (Strychnos ligustrina Blume), are gaining attention for their potential antimalarial and immunomodulatory properties, offering promising alternatives to combat drug-resistant malaria. Objective: This study aimed to evaluate the effect of ethanolic extracts from the stem of Songga wood (EESWS) on the modulation of TNF-α in malaria treatment with ACTs. Methods: A study used a post-test-only-control-group design with simple-random-sampling involved two treatment groups and three control groups, each with five Swiss-Webster mice. The C1 group was the healthy control, the C2 group was untreated, and the C3 group received ACT. The P1 group was given EESWS at preventive and therapeutic doses, while the P2 group received a combination of EESWS-ACT. Blood samples were collected on the day of the 8th infection to assess parasitemia percentage and plasma TNF-α levels. Results: On day 7 of PbA infection, the untreated C2 group exhibited the highest parasitemia levels (13.20 ± 4.18), while the C3, P1, and P2 groups showed significantly lower levels, with no significant differences among these treated groups (p > 0.05). Significant differences in TNF-α levels were observed, with the untreated C2 group having higher levels compared to the healthy C1 group and all treatment groups. Among the treatments, the P1 group had higher TNF-α levels than both the P2 and C3 groups, while no significant difference was observed between the C3 and P2 groups. Conclusions: All treatment regimens effectively promoted recovery from PbA infection, and the combination of EESWS with ACT appears to facilitate a more balanced modulation of inflammatory responses during the malaria recovery phase.